Consumer Dissatisfaction dan Variety Seeking sebagai Determinan Brand Switching: Systematic Literature Review - Amirah Cetta Candraningtyas (MDP Student Conference, 2026)
Brand switching behavior has become a common phenomenon in increasingly competitive and dynamic markets. This study aims to examine the role of consumer dissatisfaction and variety seeking as determinants of brand switching behavior through a Systematic Literature Review (SLR) approach. The review process involved identifying and selecting relevant scholarly articles from national and international journal databases based on predefined inclusion and exclusion criteria. A total of 10 articles were analyzed to identify patterns, consistencies, and discrepancies in previous research findings. The synthesis results indicate that consumer dissatisfaction consistently has a positive effect on brand switching behavior, particularly in product and service contexts that emphasize functional performance. Meanwhile, variety seeking is found to encourage brand switching even in the absence of dissatisfaction, especially among younger consumers and in product categories with low switching costs. This study concludes that consumer dissatisfaction and variety seeking complement each other in explaining brand switching behavior, highlighting the importance of an integrative perspective in understanding consumer behavior dynamics.